STRATEGI PENINGKATKAN PENDAPATAN PADA USAHATANI SAYUR SISTEM HIDROPONIK DI KOTA KENDARI - Firman Abidin; Hartina Batoa; Mardin Mardin (Universitas Halu Oleo, 2023)
This study aims to determine farmer strategies in increasing income in hydroponic system vegetable farming in Kendari city and to find out how much income hydroponic farmers in Kendari city have. The time of research was conducted in January 2023 with a total of 25 respondents who were hydroponic vegetable farmers identified at the Kendari City Agriculture Service. Data analysis used SWOT analysis and income analysis. The results of the study show that the weighting and weighing of internal and external factors can produce coordinates 0.3 and 0.32 where the coordinates are in quadrant 1, so this supports a progressive strategy or SO strategy. This strategy provides prime and stable conditions so that it is possible to continue to expand, increase growth and achieve maximum progress in hydroponic vegetable farming in Kendari City. The results also showed that the average income level in hydroponic vegetable farming was IDR 15,001,412, with an average number of planting holes of 6,740.